THE NEED FOR AN INNOVATIVE APPROACH TO THE DEVELOPMENT OF STUDENTS' PHYSICAL CULTURE (International Conference on Economics, Finance, Banking and Management, 2025)
The topic of the need for an innovative approach to the development of physical culture of students is aimed at increasing the importance of physical education and sports activities in the modern education system. This study studies the effectiveness of using innovative methods and technologies for the development of physical culture. It is envisaged to use new methodologies, interactive trainings and digital platforms to form a healthy lifestyle among students, increase physical activity and increase interest in sports. The goal is to identify the importance of innovative approaches to the development of physical culture of students, eliminate their negative factors and organize the physical education process more effectively. The results of the study will help develop new strategies for the development of physical culture in educational institutions and stimulate healthy competition among students. This topic serves to support not only the physical health of students, but also their mental and social development.